A hydrodynamic atomic force microscopy flow cell for the quantitative measurement of interfacial kinetics: The aqueous dissolution of salicylic acid and calcium carbonate - Coles, B; Compton, R; Suarez, M; Booth, J; Hong, Q; Sanders, G (1998)
A novel liquid flow cell allows atomic force microscopy (AFM) images to be obtained under defined hydrodynamic flow conditions, enabling reaction fluxes calculated from proposed heterogeneous reaction mechanisms to be compared with those determined experimentally. The cell employs an inclined jet to direct a fluid flow at the sample surface to cover the area under investigation including the AFM scanning cantilever tip. The flow pattern and velocity were calculated by using the finite element fluid dynamics program FIDAP and confirmed by placing an electrode at the sample position and measuring the limiting current for the one-electron oxidation of potassium hexacyanoferrate(II) in water as a function of flow rate. The operation of the cell has been further confirmed by the direct measurement of the dissolution rate of calcite exposed to a flow of 0.98 mM aqueous HCl by deducing the rate of removal of the surface from the change of the z-piezo voltage. The rate constant k1 = 0.035 cm s-1 obtained for the dissolution step was in excellent agreement with the value (0.043 ± 0.015) cm s-1 found from independent channel flow cell experiments. The dissolution of the (110) and (110) faces of salicylic acid (SA) single crystals in water and in solutions of salicylic acid was studied as a function of flow rate and was found to be consistent with a model combining a constant rate of dissolution with a simultaneous reprecipitation having a first-order dependence on [SA]0, with the flux J = kd - kp[SA]0 where the parameters are kd110 = 3 × 10-9 mol cm-2 s-1 and kp110 = 1.74 × 10-4 cm s-1 for the (110) face and kd110 = 1.5 × 10-8 mol cm-2 s-1 and kp110 = 1.06 × 10-3 cm s-1 for the (110) face.